The Development of Support System for the Treatment of NCD Patient with Depression Illness using the Integrated Reminiscence Program on Depression, Self-Esteem, and Quality of Life in Elderly People at Huasai Hospital, Nakhon Si Thammarat Province - Na Nakhon, Yuttapong (Region 11 Medical Journal, 2020)
Background: Depression is common problem among elderly people with chronic NCDs. Physical therapy in combination with psychosocial therapy will improve the quality of life in the elderly people. Objectives: This research aims to 1) study depression situations in the elderly,2) develop the integrated reminiscence program, and 3) study the effect of the integrated reminiscence program on depression, self-esteem and quality of life in the elderly. Method: This research and development. The population is the outpatient department, Non communicable disease clinic at Hua Sai Hospital during May to August 2020. The sample of this research were 322 elderly patients with depression selected by by Krejcie & Morgan tables. The data were collected using the Thai geriatric depression scale (TGDS). The simple sampling of 25 subjects from 13 - 24 points with TGDS for participated in the integrated reminiscence program which consists of 5 activities, 60-90 minutes each session. The questionnaires used for data collection were TGDS, Self – esteem and quality of life. Data analyzed by paired t-test. Results: The mean score of depression in elderly were 18.68 (S.D. = 3.41), 7.68 (S.D. = 1.99) before and after experiment respectively, which was statistically significantly in depression (t = 14.832, p <0.001). The elderly who receiving the reminiscence program had a statistically significant increase in their self-esteem score (t = -13.207, p <0.001) and the mean quality-of-life score had a statistically significant increased (t = -7.43, p <0.001) Conclusion: The results of this research show that the reminiscence program could reduce depression in the elderly with chronic NCDs. It increased self-esteem and quality of life.